2009
DOI: 10.1002/ibd.20756
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Crohnʼs Disease in QuéBec, Canada

Abstract: The identified predictors of CD explained 20% of the regional variance in the incidence rate of CD in the Québec population. Other factors such as genetic susceptibility to CD or the effect of an environmental cause should be taken into consideration in the models to explain the residual variance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…There was a significantly higher incidence of ulcerative colitis cases in males over the age of 50 years compared to females in the COPD cohort. Our findings are in agreement with the sex distribution of IBD in the general population [9,10,30]. The age-specific sex distribution in Crohn's disease incident cases and the predominance of female subjects (64%) in the asthma cohort also reflect the higher number of female patients with asthma in Québec [11].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was a significantly higher incidence of ulcerative colitis cases in males over the age of 50 years compared to females in the COPD cohort. Our findings are in agreement with the sex distribution of IBD in the general population [9,10,30]. The age-specific sex distribution in Crohn's disease incident cases and the predominance of female subjects (64%) in the asthma cohort also reflect the higher number of female patients with asthma in Québec [11].…”
Section: Discussionsupporting
confidence: 89%
“…A study addressing the epidemiology of Crohn's disease in Québec has shown that a proportion of immigrants above 10% in health-related geographical divisions was associated with a significantly lower incidence of Crohn's disease; in contrast, a proportion of Jewish descendants above 20% was associated with a significantly increased incidence of Crohn's disease [9]. Further studies in other geographical locations may be needed to confirm such findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the incidence of UC was high; an equally high incidence has so far only been reported in Iceland. 20 The incidence of CD was comparable to those rates seen in Northern Europe 8,12,16,17 and France, 21 but lower than in Canada [22][23][24] and New Zealand. 25 The highest incidence rates were seen in the age group 15-24 years in CD and in the age group 25-34 in UC, as shown in many studies.…”
Section: Discussionsupporting
confidence: 59%
“…Girls were 25% less likely to develop IBD as previously observed, and our overall IBD incidence rate (1.2/10 000 person-years) was similar to previous populationbased incidence rate estimates among children. 29 Those with extreme social deprivation were less likely to develop IBD, consistent with the "hygiene hypothesis" (persons living in cleaner environments may be more likely to develop autoimmune disorders). 30 Chronic granulomatous disease and primary sclerosing cholangitis, both known to be associated with IBD, were highly but imprecisely associated with IBD, reflecting their rarity.…”
Section: Discussionmentioning
confidence: 51%